The Analysis of Online Brand Community, Online Perceived Brand Reputation, Brand Trust, Brand Loyalty at Cafe Businesses Based in Surabaya - Felyshia Aditya Kurniawan; Michael Adiwijaya (Master of Management, School of Business and Management, Petra Christian University, 2018)
The internet has become a human lifestyle. Many business people took advantage of this opportunity to market their business by using social media marketing strategy on Facebook or Instagram. Activities in the online brand community on social media platforms could build consumer perceptions of a brand inside the online world and would form a belief in the brand that ultimate to loyalty. Therefore, social media marketing must be known for its effectiveness. This study aims to determine the influence of the online brand community on online perceived brand reputation, brand trust, and brand loyalty at cafes in Surabaya. The method used in this study is quantitative by spreading the questionnaires to 240 respondents of college students both online and offline. The research using purposive sampling technique and the sample used in this research is the consumers of De Mandailing Cafe & Eatery, Panties Pizza, and Warunk Upnormal in Surabaya where the three cafes are considered to represent the whole cafes with the same quality, consumers, service system, and price range. From the results of this study, it can be concluded that online brand community has a significant impact on brand loyalty through online process perceived brand reputation and brand trust.